Effects of TiO₂ nano-priming and field capacity levels on germination and growth of cayenne pepper (Capsicum frutescens) - NUR ANINDYA RAHMAWATI; SOLICHATUN SOLICHATUN; ARI PITOYO (Asian Journal of Agriculture, 2026)
Abstract. Rahmawati NA, Solichatun, Pitoyo A. 2026. Effects of TiO₂ nano-priming and field capacity levels on germination and growth of cayenne pepper (Capsicum frutescens). Asian J Agric 10 (1): g100112. https://doi.org/10.13057/asianjagric/g100112. Capsicum frutescens is a vital crop in Indonesia but suffers from seasonal yield instability due to water stress. This study explored nano-priming with titanium dioxide nanoparticles (TiO₂NPs) to improve seedling resilience. The experiment was conducted in two stages. In the germination stage, four TiO₂NP concentrations (0%, 2%, 4%, and 8%) were tested on seed germination using a Completely Randomized Design (CRD). In the growth stage, seedlings were subjected to a 4 × 3 factorial CRD combining the same TiO₂NP concentrations with three levels of water availability (100%, 75%, and 50% field capacity), with three replicated. Data were analyzed using two-way ANOVA and Duncan’s Multiple Range Test (p < 0.05). During germination, nano-priming with 4% TiO₂NP accelareted germination rate (5.3 days) and enhanced sprout length (6.68 cm), whereas the control exhibited slower germination (9.03 days) and shorter sprouts (2.60 cm). In the subsequent growth phase, TiO₂NPs significantly influenced seedling height, shoot-to-root ratio, and proline content. The tallest seedling was observed at 8% TiO₂NP, particularly under 75% field capacity. In contrast, optimal shoot-to-root ratio and elevated proline accumulation were associated with 2% TiO₂NP under 100% and 75% field capacity, respectively. These finding demonstrated that TiO2NP nano-priming exerts stage-dependent effects, with distinct concentrations optimizing germination performance and drought-related physiological responses during early seedling growth, highlighting its potential as a scalable approach for improving C. frutescens cultivation under water-limited conditions.